Tratamentos de fibras de carnaúba [copernicia prunífera (miller) h. e. moore] para o desenvolvimento de compósito biodegradável com matriz de polihidroxibutirato - Carvalho, Luiz Fernando Meneses (2011)
The use of raw materials from renewable sources for production of materials has been the subject of several studies and researches, because of its potential to substitute petrochemical-based materials. The addition of natural fibers to polymers represents an alternative in the partial or total replacement of glass fibers in composites. In this work, carnauba leaf fibers were used in the production of biodegradable composites with polyhydroxybutyrate (PHB) matrix. To improve the interfacial properties fiber / matrix were studied four chemical treatments to the fibers..The effect of the different chemical treatments on the morphological, physical, chemical and mechanical properties of the fibers and composites were investigated by scanning electron microscopy (SEM), infrared spectroscopy, X-ray diffraction, tensile and flexural tests, dynamic mechanical analysis (DMA), thermogravimetry (TGA) and diferential scanning calorimetry (DSC). The results of tensile tests indicated an increase in tensile strength of the composites after the chemical treatment of the fibers, with best results for the hydrogen peroxide treated fibers, even though the tensile strength of fibers was slightly reduced. This suggests a better interaction fiber/matrix which was also observed by SEM fractographs. The glass transition temperature (Tg) was reduced for all composites compared to the pure polymer which can be attributed to the absorption of solvents, moisture and other low molecular weight molecules by the fibers